The mediating role of public belonging in the relationship between competitive sports participation, loneliness, and self-harm among adolescents - Liang, Yadong; Chen, Chunming; Liu, Shangguozi (Frontiers in Psychiatry, 2026)
IntroductionLoneliness and self-harming behaviors among adolescents are central concerns in global public health and education. While sports participation is known to promote well-being, the underlying mechanisms remain underexplored. Drawing on social identity theory, this study investigates whether participation in competitive sports enhances adolescents’ sense of public belonging, thereby reducing loneliness and self-harm.MethodsA quasi-experimental study was conducted with 90 middle school students randomly assigned to intervention or control groups. Over six weeks, the intervention group participated in team-based competitive sports (football, basketball, volleyball), while the control group continued regular physical education. Measures included the Psychological Sense of School Membership (PSSM), UCLA Loneliness Scale (ULS), and Self-Harm Behavior Questionnaire (SHBQ). Data were analyzed using independent-sample t-tests, structural equation modeling (SEM), and mediation analysis.ResultsCompetitive sports significantly increased students’ sense of public belonging. Belonging was associated with reduced self-harm and lower loneliness scores. However, within SEM, the belonging–loneliness path was only marginally significant. Overall model fit indices were weak, suggesting more complex underlying processes.ConclusionsFindings indicate that competitive sports reduce adolescents’ risk of self-harm primarily by enhancing their sense of public belonging. Evidence for buffering loneliness was weaker, implying that loneliness is shaped more directly by family, peers, and broader resources. Theoretically, this extends social identity and social capital frameworks in sport psychology. Practically, it cautions that focusing solely on performance may cause schools to overlook sports’ social benefits, limiting long-term effectiveness. Promoting adolescent mental health will require integrating school-based sports with family support, community engagement, and psychological services to build a more sustainable system of care.